John J. Ballentine papers - Ballentine, John J. (John Jennings), 1896-1970.
Correspondence, memoranda, diaries, logbooks, military records, biographical materials, scrapbooks, clippings, photographs, and other papers relating primarily to Ballentine's naval career after 1920.
Documents Ballentine's training as an air pilot; his duties at the Naval Proving Ground, Dahlgren, Va., including the testing of the Norden bombsight and the first remote-controlled airplane; his correspondence with Theodore H. Barth, president of Carl L. Norden, Inc., relating to the testing and production of Norden bombsights; his activities during World War II off the coast of North Africa during Operation Torch (1942) and as first commanding officer of the Bunker Hill (aircraft carrier) in campaigns in the Pacific Ocean (1943-1944); his postwar tours of duty in the Mediterranean as commander of Carrier Division One (1947-1949) and as commander of the Sixth Fleet (1949-1951); his tour of duty (1951-1954) as Commander Air Force Atlantic Fleet (COMAIRLANT); his activities as a member of a U.S. armed forces interservice board in Washington, D.C. (1956-1957); and his lifelong interest in hunting. Correspondence received as COMAIRLANT includes reports from commanders in the Mediterranean and information on the Korean War. Includes histories of U.S. naval aviation.
Library of Congress Prints and Photographs Division.
U.S. naval officer and air pilot.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Barth, Theodore H. -- 1891-1967 -- Correspondence; United States. -- Navy -- Aviation; United States. -- Navy -- Foreign service -- Atlantic Ocean; United States. -- Navy -- Foreign service -- Mediterranean Region; United States. -- Navy -- Officers; United States. -- Navy. -- Atlantic Fleet. -- Air Force; United States. -- Navy. -- Carrier Division One; United States. -- Navy. -- Fleet, 6th.; Bunker Hill (Aircraft carrier : CV-17); Carl L. Norden, Inc; Naval Proving Ground (Dahlgren, Va.); Aeronautics, Military; Airplanes, Military -- Flight testing; Flight; Flight training; Hunting; Korean War, 1950-1953.; Norden bombsight; Operation Torch, 1942.; Remote control; World War, 1939-1945 -- Aerial operations, American; World War, 1939-1945 -- Campaigns -- Africa, North; World War, 1939-1945 -- Campaigns -- Pacific Ocean; World War, 1939-1945 -- Naval operations, American; United States -- Armed forces; Aviators; Naval officers